2019
DOI: 10.1111/cas.13998
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts contribute to cisplatin resistance by modulating ANXA3 in lung cancer cells

Abstract: Cancer tissues consist of cancer cells, surrounding stromal cells and the extracellular matrix. Cancer‐associated fibroblasts ( CAF ) are one of the key components of stromal cells. CAF have a great impact on the behavior of cancer cells, including proliferation, invasion, metastasis and chemoresistance in many ways. However, the underlying mechanism had not been fully elucidated. In this study, we investigated the role of CAF in cisplatin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 37 publications
1
61
3
Order By: Relevance
“…The findings obtained thus far point towards a potential use of ANXA3 as a diagnostic, prognostic and predictive biomarker for cancer patient management 38–41 . More relevant to the sepsis profiling data presented and discussed here, mechanistic studies point to a role played by ANXA3 in promoting cancer growth and metastasis 42–45 . Notably, a recent study also reported benefits of anti‐ANXA3 monoclonal antibodies in a preclinical mouse model of HCC 45 .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The findings obtained thus far point towards a potential use of ANXA3 as a diagnostic, prognostic and predictive biomarker for cancer patient management 38–41 . More relevant to the sepsis profiling data presented and discussed here, mechanistic studies point to a role played by ANXA3 in promoting cancer growth and metastasis 42–45 . Notably, a recent study also reported benefits of anti‐ANXA3 monoclonal antibodies in a preclinical mouse model of HCC 45 .…”
Section: Resultsmentioning
confidence: 59%
“…49 It is notable that, on one hand, improved tumour-cell survival and proliferation was shown to be mediated, in part, by ANXA3-mediated caspase 3 (CASP3) suppression. 45,50,51 And in vascular smooth muscle cells a decrease in CASP3 levels was also shown to accompany inhibition of apoptosis and increased proliferation induced by ANXA3. 52 On the other hand, CASP3 is also well-known to mediate neutrophil programmed cell death: indeed over 1000 records being returned by the PubMed query: neutrophil* AND ('Caspase 3' OR CASP3).…”
Section: Additional Reference Datasets Inform On Anxa3 Restriction Anmentioning
confidence: 97%
“…In addition to CAM-DR, interactions between stromal and tumor cells can also modify the ECM and secret growth factors, support tumor angiogenesis, suppress anticancer immune response, and therefore produce a TME niche that promotes drug resistance. Carcinoma-associated fibroblasts (CAFs) are the predominant cell type within the TME, and their associations with CDDP resistance have been widely explored [73,74,75,76,77,78]. In most studies using CAF coculture methods, tumor cells obtained CDDP resistance through CAF-secreted chemokines or growth factors, such as interleukin (IL)-6, IL-8, IL-11, insulin-like growth factor 1, or transforming growth factor-β (TGF-β).…”
Section: Emerging Perspectives On Cddp Resistance From the Tmementioning
confidence: 99%
“…Instead, CAFs epigenetically downregulate caspase expression, inducing transcription factor STAT1, thus limiting caspases 9, 3 and 7 activation. In in vitro and in vivo lung cancer models, CAFs secretion of Annexin A3 has been shown to stimulate cancer cells survivin, known to inhibit caspases activity, thus leading to the decrease in caspases 3 and 8 cleavage under cisplatin treatment [ 44 ]. Similarly, CAFs protect lung and ovarian cancer cells from cisplatin via increasing survivin by promoting STAT3 phosphorylation [ 32 , 33 ].…”
Section: Cafs Sustain Cancer Cells Mitochondriamentioning
confidence: 99%